From Twitter to X. The risk of reliance on private sources for research - Piñeiro-Otero, Teresa (Anuario ThinkEPI, 2023)
Academic research is deeply rooted in its social, economic, political, and cultural contexts. At a time of expansion and diversification of the digital sphere, social platforms, especially Twitter, are key tools for communication research. The evolution of the Twitter API has significantly facilitated the collection of big data for communication research. However, the recent limitation of free access to this tool poses, with the change in X’s corporate policies, important challenges that require rethinking dependence on private sources as well as the development of adaptive research strategies.
Keywords: Twitter; API; Research; Source dependence; Data